Examination of students' acceptance of and intention to use learning management systems using extended TAM - Eraslan Yalcin, Muyesser; Kutlu, Birgul (British journal of educational technology, 2019)
The aim of this study is to examine students’ acceptance of and intention to use Learning Management Systems (LMSs) for university education in Turkey using extended Technology Acceptance Model (e‐TAM). TAM has been widely used in various fields of technology acceptance in the last years and is found to be highly useful for the determination of the factors influencing the intention to use and adopt e‐learning platforms at universities. However, studies in this field have not converged around a uniform version of TAM. Almost all studies used different factors, samples or technologies to study behavioral intention. In this study, the most commonly used factors are compiled in one model. Results show that intention to use a LMS is affected from perceived usefulness, perceived ease of use and social norm. At the same time, perceived usefulness is affected from perceived ease of use, social norm and user interface design and perceived ease of use is affected from user interface design and computer self‐efficacy. Practitioners Notes What is already known about this topic E‐TAM is successfully applied to various e‐learning platforms (such as Moodle, Blackboard, IWiLL web‐based learning system, gadgets and etc.) to examine students’ acceptance and intention to use. According to the literature, the external variables are various, and social norm, user interface design and computer self‐efficacy are most commonly used or suggested factors. What this paper adds In this study, most common factors, which were not used altogether in one framework in other studies, are used to discover the behavioral intention to use a learning management System (LMS). The model is applied to two different sample groups by taking into consideration adoption issues. The proposed model of this study is analyzed by SEM technique to confirm the path and to find the best model fitting values. Implications for practice and/or policy Using this model the learning environment will improve and it will attract students more that will increase their intention to use LMS. This study would help universities to increase LMS usage by considering social norms, user interface design and computer self‐efficacy.